Labour defenselessness and school management. Measure and prevalence - Tejero González, Carlos María; Fernández Díaz, María José (Avances en Supervisión Educativa, 2009)
This article analyses the labour defenselessness in school management as it is acquired by School headteachers in office, and considered as a feeling of helplessness by them when their labour expectations suffer lack of control and poverty of results. A useful scale to measure up the level of labour defenselessness is provided here, as well as some data to prove that school headteachers do not feel themselves defenceless as labour is concerned.